Non-retroactivity of tax regulations and the First Complementary Disposition of Legislative Decree 1421 - Bardales Castro, Percy Enrique (2022)
This paper aims to offer some brief reflections on the legal effect generated by the entry into force of the First Transitory Complementary Provision of the Legislative Decree 1421 for purposes of the regulatory regime related to the start of the statute of limitation for the exercise of the power of the tax authority to demand payment of the tax debt, as amended by Legislative Decree 1113.